Odpowiedzi

Najlepsza Odpowiedź!
2009-10-30T18:53:14+01:00
A)x(x+2)+1=(x+1)(x+1)
x²+ 2x +1 = x² + 2x + 1
0=0
zawsze prawdziwe
b)(x-1)(1+x)=1-x2
(x-1)(x+1)= 1-x²
x²-1 = 1-x²
2x² = 2
x²=1
x=1 lub x =-1
nie zawsze prawdziwe, prawdziwe tylko dla 1 lub -1
c)(x-2)(x+1)=(x+2)(x-1)-x
x² +x -2x -2 = x² - x + 2x -2 -x
x-2 = 2x -2
x = 2x
-x=0
x=0
nie zawsze prawdziwe, prawdziwe tylko dla x =0
d) (x+5)(x+5)=(x-5)(x-5)+20x
x² + 10x + 25 = x² - 10x + 25 +20 x
20x = 20x
0=0
zawsze prawdziwe
2009-10-30T19:00:31+01:00
A)x(x+2)+1=(x+1)(x+1)
x²+2x+1=x²+2x+1
spr. dla x=1
1+2+1=1+2+1
4=4 prawdziwa

b)(x-1)(1+x)=1-x2
x+x²-1-x=1-x²
x²-1=1-x²
spr. dla x=0
-1≠1 nieprawdziwa

c)(x-2)(x+1)=(x+2)(x-1)-x
x²+x-2x-2=x²-x+2x-2-x
x²-x-2=x²-2
spr. dla x=3
9-3-2=9-2
4≠7nieprawdziwa
d) (x+5)(x+5)=(x-5)(x-5)+20x
x²+10x+25=x²-10x+25+20x
x²+10x+25=x²+10x+25
spr. dla x=0
25=25 prawdziwa